Pengaruh Pengungkapan Emisi Karbon, Profitabilitas, dan Struktur Modal terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to evaluate the impact of carbon emission disclosure, profitability levels, and capital structure on firm value with a focus on manufacturing companies in the energy sector listed on the Indonesia Stock Exchange (BEI). To measure carbon emission disclosure, this study uses indicators compiled based on the list from the Carbon Disclosure Project (CDP) adapted by (Bae Choi et al., 2013). Meanwhile, profitability is measured by ROA, capital structure by DER, and firm value by PBV, as stated in the annual financial reports of each entity. This research refers to signaling theory which emphasizes the importance of conveying information from the company's internal to external stakeholders. One form of that information is carbon emission disclosure, which is considered a strategic signal in supporting corporate sustainability and transparency. The research sample consists of 15 energy companies active registered at the IDX during the period 2019-2023, resulting in 75 data observations. The analysis method used is multiple linear regression. The research results show that carbon emissions do not have a significant effect on the value of the company. On the contrary, profitability and capital structure are proven to have a positive and significant impact on increasing the company's value.